A classical-Marxian model of antebellum slavery. (17th February 2018) - Clegg, John; Foley, Duncan
Abstract: This paper outlines a classical–Marxian model of the antebellum US economy. The model assumes that the mobility of capital tended to equalize the rate of profit between North and South, whilst land rents were minimized by an expanding frontier. Under these conditions slave prices are the capitalized present value of the excess surplus value produced by slaves. This excess surplus value arose because slaves could be forced to work harder at a lower standard of subsistence than wage laborers, who were free to move between individual employers and also between sectors by farming frontier lands. If the growth of the slave population saturated the land available for slave production, land rents would rise to capture the excess surplus value produced by slaves, and slave prices would collapse. We find the model predicts historical movements of slave prices, and is compatible with contemporaneous views of the impact of territorial restriction on the viability of slavery.